Influência do treinamento físico aeróbio sobre a morfologia e função cardíaca de ratos resistentes à obesidade - Cordeiro, Jóctan Pimentel (2016)
Few studies have assessed the cardiac function in obesity resistance (OR) models. The mechanisms involved in calcium transient in cardiac dysfunction in OR mouse models are not well determined. This study was designed to test the hypothesis that the unsaturated fat diet promotes myocardial dysfunction in OR rats and this damage is observed in extracellular Ca2+ transient. However, some tools have been used as an intervention factors for both prevention and treatment of heart disease, among them, stands out the physical training (PT) as non-pharmacological intervention. In the present study, we used 80 male Wistar rats, 30 days old, and subjected to exposure and induction protocol obesity, 5 weeks of induction and 15 weeks of exposure to obesity, a total of 20 consecutive weeks. The rats were randomized into two groups: a) SD: standard diet fed (n = 40) and b) HFD: fed with unsaturated high fat diet (n = 40). The animals were redistributed as the absence or presence of aerobic PT moderate intensity (70% of TVM) for 12 weeks. In the second stage of the experimental protocol, the study consisted of four groups: control (C, n = 12), control submitted to the physical training protocol (CPT; n = 14), obesity-resistant (OR; n = 9) and obesity-resistant subjected to physical training protocol (ORPT; n = 10). They were analyzed: body weight (BW), body fat percentage (BF%), adiposity index, nutritional and metabolic parameters and systolic blood pressure (SBP). The process of cardiac remodeling was assessed by post mortem macroscopic and microscopic studies. The cardiac function analysis was performed in vitro by means of maneuvering inotropic and lusitropic using the isolated papillary technique muscle of the LV. The comparison of the experimental groups was performed by ANOVA for two factors, supplemented with multiple comparison test of Bonferroni. The level of significance for all variables was 5%. After 32 weeks of experimental protocol, OR animals group showed weight gain, final body weight, sum of fat deposits and adiposity index similar to group C. However, OR showed glucose intolerance and increased serum levels of LDL. The OR animals showed no change in the behavior of SBP and HDL. Macroscopic post mortem study showed that OR has lower weight values of the heart chambers and total heart, a fact, evidenced by lower deposition of interstitial collagen, with preserved cross-sectional area of LV cardiomyocytes. In addition, in vitro cardiac function was not impaired in animals OR. Aerobic PT moderate intensity was effective in decreasing the majority of body composition parameters related to fat deposition and normalized the elevated serum LDL levels observed in the sedentary animals OR. However, it was not able to decrease glucose intolerance in these animals. PT did not changed both morphology as cardiac function. However, OR rats when subjected to unsaturated HFD for a long period and PT seem to have increased their pressure values. In conclusion, the OR animals subjected to prolonged unsaturated HFD period have dyslipidemia, glucose intolerance and lower heart by less collagen deposition, without reducing the cardiac function. Aerobic PT did not change the morphology and cardiac function.